2017
DOI: 10.3389/fnbeh.2017.00207
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Over-Activation by Social Defeat Stress Contributes to Anxiety- and Depressive-Like Behaviors

Abstract: Hyper activation of the neuroimmune system is strongly related to the development of neuropsychiatric disorders. Psychosocial stress has been postulated to play an important role in triggering anxiety and major depression. In preclinical models, there is mounting evidence that social defeat stress activates microglial cells in the central nervous system. This type of stress could be one of the major factors in the development of these psychopathologies. Here, we reviewed the most recent literature on social de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 62 publications
4
78
0
Order By: Relevance
“…Microglial activation with subsequent inflammatory cytokine release also mediates the effects of stress [29][30][31]; these processes have been implicated as a major trigger of depression in both human and animal models [32][33][34]. At different stages of depression, the functional status of microglia is diverse, and they exert different regulatory effects on neurons in different functional states [30,31,35].…”
Section: Introductionmentioning
confidence: 99%
“…Microglial activation with subsequent inflammatory cytokine release also mediates the effects of stress [29][30][31]; these processes have been implicated as a major trigger of depression in both human and animal models [32][33][34]. At different stages of depression, the functional status of microglia is diverse, and they exert different regulatory effects on neurons in different functional states [30,31,35].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there are several studies disclosed its potential on the progression of neurological diseases, such as multiple sclerosis and neuropathic pain, by modulating the function of dendritic cells and microglial cells. Latest reports suggest that microglial cells are actively engaged in the regulation of emotional behavior . Moreover, it has been reported that microglial P2Y 12 is essential for the modulation of synaptic plasticity in mouse visual cortex .…”
Section: Introductionmentioning
confidence: 99%
“…Latest reports suggest that microglial cells are actively engaged in the regulation of emotional behavior. 9,10 Moreover, it has been reported that microglial P2Y 12 is essential for the modulation of synaptic plasticity in mouse visual cortex. 11 Therefore, it is possible that P2Y 12 may be involved in the regulation of neurobehavior such as emotion and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…The HPA axis and the immune system are interconnected and communicate with the central nervous system 282 . Both are implicated in stress-related disorders, as alterations of these systems occur both in peripheral tissues and in the brain with stress exposure [282][283][284][285] . In suicide victims with MDD, an increase in proinflammatory cytokines, hyperactivated microglia, and elevated brain macrophages have been seen [286][287][288] .…”
Section: Chapter IIImentioning
confidence: 99%